Improvement in Stereoacuity After Refractive Correction in Astigmatic Children: A Cross-Sectional Study: Improvement in Stereoacuity after Refractive Correction in Astigmatic Children - Khan, Sufian Ali; Shah, Mutahir; Khattak, Irfan Aslam; Khalid, Ayesha; Vaqar, Abeer; Qureshi, Maliha Akhtar; Ahmad, Nafees (Pakistan Journal of Health Sciences, 2025)
Uncorrected astigmatism in children is a major cause of visual impairment, often associated with reduced stereopsis and visual symptoms, which may be further exacerbated by prolonged screen exposure. Objectives: This study aimed to evaluate the effect of full refractive correction on stereopsis in children with moderate-to-high astigmatism and to examine the association between cylindrical error, screen time, and stereoacuity. Methods: A cross-sectional study was conducted among 273 children aged 4–8 years attending the ophthalmology department of KRL hospital, Islamabad. Consecutive sampling was employed. After ethical approval and informed consent, each participant underwent a comprehensive ocular examination, including visual acuity testing with ETDRS charts and stereopsis assessment using vectograph circles. Demographic data, refractive status, screen exposure, and outdoor activity were recorded. Statistical analysis included Spearman’s correlation and the Wilcoxon Signed-Rank Test. Results: The mean uncorrected stereopsis was 141.5 ± 108.1 arc seconds, improving significantly to 66.8 ± 36.6 arc seconds after optical correction (Z=–14.031, p<0.001). A significant positive correlation was found between cylindrical error in the right eye and baseline stereopsis (Spearman’s rho=0.465, p<0.001). Screen time averaged 4.9 ± 1.5 hours/day. Asthenopic symptoms, including frequent blinking (82.4%) and blurred vision (81.0%), were highly prevalent. Conclusion: Full refractive correction significantly improves stereopsis in children with high astigmatism. Excessive screen exposure may further compromise binocular function, underscoring the importance of early detection, timely correction, and lifestyle modifications in pediatric populations.